Carboxytherapy in the light of the latest reports. Erythema multiforme-like eruption as a side effect of carboxytherapy - Barańska-Rybak, Wioletta; Mehrholz, Dorota M. (Dermatology Review/Przegląd Dermatologiczny, 2019)
Carboxytherapy is a very popular method applied in aesthetic medicine. The procedure is used for the reduction of cellulite, atrophic scarring and stretch marks, treatment of localized adiposities, wrinkle correction and rejuvenation of the skin. It is claimed that carbon dioxide therapy is a very safe procedure with only a small number of complications. Pain, oedema and bruising of the injection area are often side effects of carboxytherapy. There are only a few reports of more serious complications such as subcutaneous emphysema or Mycobacterium infection. The following is the first case report of herpes-associated erythema multiforme caused by carboxytherapy. A 41-year-old woman consulted a dermatologist because of erythematous skin lesions with brightening in the central part of the macules which appeared three days after the carboxytherapy. In the anamnesis recurrent herpes labialis was noted.